2017
DOI: 10.24820/ark.5550190.p010.288
|View full text |Cite
|
Sign up to set email alerts
|

Recent applications of aziridine ring expansion reactions in heterocyclic synthesis

Abstract: The inherent reactivity of the aziridine ring due to ring-strain makes it valuable building blocks for the synthesis of other heterocyclic motifs of biological relevance. Of particular significance is the generation of azomethine ylides from them and cycloaddition of ylides with alkenes, alkynes, and heterocumulenes. The ring undergoes opening followed by cyclization with a variety of reagents either in the presence of a catalyst or without any catalyst. This review article discusses the recent applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 126 publications
1
14
0
Order By: Relevance
“…A large number of synthetic methodologies have been developed to the access of azaheterocycles including aziridines, azetidines, pyrrolidines, piperidines or azepanes . In organic and pharmaceutical chemistry, the creation of novel saturated N ‐heterocycles is a field explored deeply.…”
Section: Synthesis Of Saturated N‐heterocycles From Dialdehyde Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of synthetic methodologies have been developed to the access of azaheterocycles including aziridines, azetidines, pyrrolidines, piperidines or azepanes . In organic and pharmaceutical chemistry, the creation of novel saturated N ‐heterocycles is a field explored deeply.…”
Section: Synthesis Of Saturated N‐heterocycles From Dialdehyde Compoundsmentioning
confidence: 99%
“…A large number of synthetic methodologies have been developed to the access of azaheterocycles including aziridines, azetidines, pyrrolidines, piperidines or azepanes. [31][32][33][34][35] In organic and pharmaceutical chemistry, the creation of novel saturated N-heterocycles is a field explored deeply. However, due to the increasing importance of these scaffolds, the development of novel, efficient, cost effective, selective, and stereocontrolled protocols for these derivatives is a continuous challenge in modern chemistry.…”
Section: Synthesis Of Saturated N-heterocycles From Dialdehyde Compoundsmentioning
confidence: 99%
“…The most common lactams are four-membered (b-lactams, also known as 2-azetidinones, Fig. 1a), 1,[5][6][7][8] vemembered (g-lactams, also known as 2-pyrrolidinones, Fig. 1b), 2,9-11 six-membered (d-lactams, also known as 2-piperidinones, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Less commonly, they are also used to prepare six-membered rings. [15][16][17][18][19][20][21][22][23][24] Although azetidin-2-ones have been extensively investigated, our literature surveys revealed that isoindoles bearing a β-lactam ring at the β-position had not been reported. We therefore decided to synthesize such compounds in a highly stereoselective manner by in situ production of a novel ketene that would subsequently be trapped with various Schiff bases, and an electrocyclic reaction of a zwitterionic intermediate.…”
mentioning
confidence: 99%